PARTISIPASI PASIEN DM DAN HIPERTENSI SEBAGAI PESERTA PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) DI PUSKESMAS MENGWI 1 - Ni Luh Gde Ari Natalia Yudha; I Putu Dedy Kastama Hardy (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTNon-communicable diseases (NCD) are the leading cause of death in Indonesia. NCD is increasingly becoming a double burden that must be faced in the development of the health sector in Indonesia. Mengwi village is one of the area in Badung-Bali that has Universal Health Coverage (UHC) which covers all of its people with health services. Prolanis is one of the efforts that can be carried out to overcome this problem. This study aimed to determine the level of participation as prolanis participants in Mengwi. This study used a cross-sectional study design with 74 respondent who visited the Mengwi 1 Community Health Center and had an hypertension and diabetes mellitus symptom. We collected them by accidental sampling method using a questionnaire. The data were analyzed by chi square test. The results showed that the participation rate of respondent who did not participate in prolanis was 59.5% or 44 people while those who participated 40.5% or 30 respondent. The participation is influenced by knowledge, work, attitudes, age, education, distance, family support and health workers. There are the influence of knowledge, work attitudes, age, education, distance, family support and health workers on participation as prolanis participants. Need home visit to improved the participation of participants.Keywords: Prolanis; Community health center; NCD.ABSTRAKPenyakit Tidak Menular (PTM) menjadi penyebab kematian terbanyak di Indonesia. PTM semakin meningkat menjadi beban ganda yang harus dihadapi dalam pembangunan bidang kesehatan di Indonesia. Prolanis salah satu upaya yang bisa dilaksanakan untuk menanggulangi masalah tersebut. Tujuan penelitian ini adalah untuk mengetahui tingkat partisipasi sebagai peserta prolanis di Puskesmas Mengwi 1. Penelitian ini menggunakan rancangan penelitian cross sectional dengan sampel yaitu pasien hipertensi dan diabetes militus sebanyak 74 orang yang berkunjung ke Puskesmas Mengwi 1 diambil dengan accidental sampling. Data diambil menggunakan kuesioner dan dianalisis dengan chi squere. Hasil penelitian diperoleh bahwa tingkat partisipasi pasien yang tidak ikut prolanis sebesar 59,5% atau 44 orang sedangkan yang ikut 40,5% atau 30 orang pasien. Partisipasi pasien dipengaruhi oleh pengetahuan, sikap pekerjaan, umur, pendidikan, jarak, dukungan keluarga dan petugas kesehatan. Kesimpulan dari penelitian ini adalah ada pengaruh pengetahuan, sikap pekerjaan, umur, pendidikan, jarak, dukungan keluarga dan petugas kesehatan terhadap partisipasi sebagai peserta prolanis. Puskesmas Mengwi 1 perlu melakukan kunjungan ke rumah pasien untuk meningkatkan pastisipasi pasien.Kata kunci: Prolanis; Partisipasi; Puskesmas.